Sharing diversity: establishing and supporting community seedbanks in South Africa (pilot phase 2013-2015) - Tjikana, Thabo T.; Dibiloane, A.; Maluleke, Nkat Lettie; Moila, P.; Phora, G.; Sthapit, B.R.; Vernooy, Ronnie (Bioversity International, 2016)
A promising start has been made: the two new community seedbanks of Gumbu and Sterkspruit and complementary technical support provided by the government will allow farmers to improve seed conservation technologies, increase access to crop diversity, apply crop improvement practices and explore seed production and marketing opportunities. The Gumbu community seedbank in particular illustrates the key role of women farmers in local conservation efforts and how these efforts in turn have the potential to change the local agro-ecological and socio-economic landscape. Future work will continue to pay attention to the successes and challenges of such farmers’ efforts and continue to draw more attention and support to: encourage the safeguarding and improvement of local plant species and varieties maintained by smallholder farmers and their communities recognizing the central role of women; value and reward farmers’ collective efforts to safeguard and improve agricultural biodiversity and associated cultural values and knowledge; and support farmers technically and financially to organize themselves, and strengthen their organizational capacity taking into consideration the leadership role of women.